Differential Flavonoid and Other Phenolic Accumulations and Antioxidant Activities of Nymphaea lotus L. Populations throughout Thailand - Duangjai Tungmunnithum (2022)
Nymphaea lotus L. is a potential plant in the Nymphaeaceae family that is well-recognized as an economic and traditional medicinal plant in Thailand and other countries. Its pharmacological and medicinal effects have been confirmed. However, there is no study going deeper into the population level to examine the phytochemical variation and biological activity of each population that benefits phytopharmaceutical and medical applications using this plant as raw material. This study was intensely conducted to complete this important research gap to investigate the flavonoid profiles from its floral parts, the stamen and perianth, as well as the antioxidant potential of the 13 populations collected from every floristic region by (1) analyzing their flavonoid profiles, including the HPLC analysis, and (2) investigating the antioxidant capacity of these populations using three assays to observe different antioxidant mechanisms. The results indicated that the northeastern and northern regions are the most abundant floristic regions, and flavonoids are the main phytochemical class of both stamen and perianth extracts from N. lotus. The stamen offers higher flavonoids and richer antioxidant potential compared with the perianth. This finding is also the first completed report at the population level to describe the significant correlation between the phytochemical profiles in floral parts extracts and the main antioxidant activity, which is mediated by the electron transfer mechanism. The results from the Pearson correlation coefficients between several phytochemicals and different antioxidant assessments highlighted that the antioxidant capability of these extracts is the result of complex phytochemical combinations. The frontier knowledge from these current findings helps to open up doors for phytopharmaceutical industries to discover their preferred populations and floral parts that fit with their targeted products.